2015
DOI: 10.1186/1471-2407-15-1
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive 125I seeds inhibit cell growth and epithelial-mesenchymal transition in human glioblastoma multiforme via a ROS-mediated signaling pathway

Abstract: BackgroundGlioblastoma multiforme (GBM) is the most common primary central nervous system neoplasm in adults. Radioactive 125I seed implantation has been widely applied in the treatment of cancers. Moreover, previous clinical trials have confirmed that 125I seeds treatment was an effective therapy in GBM. We sought to investigate the effect of 125I seed on GBM cell growth and Epithelial-mesenchymal transition (EMT).MethodsCells were exposed to irradiation at different doses. Colony-formation assay, EdU assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
324
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 362 publications
(341 citation statements)
references
References 44 publications
16
324
0
1
Order By: Relevance
“…In this sense, studies performed with NHEK (normal human epidermal keratinocytes) cultivated in medium supplemented with hydrogen peroxide in intervals of 0-72 h showed that ROS induce EMT [65]. Other study, using multiple glioblastoma cells pointed out reduction in E-cadherin level expression and increasing in vimentin, actions observed during EMT [51]. These results demonstrate that cell culture systems are useful models for study EMT, once they mimic faithfully the natural history of the oncogenic process.…”
Section: Cell Culture: Useful Model To Study Emtmentioning
confidence: 78%
See 2 more Smart Citations
“…In this sense, studies performed with NHEK (normal human epidermal keratinocytes) cultivated in medium supplemented with hydrogen peroxide in intervals of 0-72 h showed that ROS induce EMT [65]. Other study, using multiple glioblastoma cells pointed out reduction in E-cadherin level expression and increasing in vimentin, actions observed during EMT [51]. These results demonstrate that cell culture systems are useful models for study EMT, once they mimic faithfully the natural history of the oncogenic process.…”
Section: Cell Culture: Useful Model To Study Emtmentioning
confidence: 78%
“…1) [46][47][48][49][50]. For this reason, cells in EMT are resistant to chemotherapies and adjuvant drugs employed in cancer treatment [41,51].…”
Section: Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Berkowitz and Lapinski 94 observed that maternal ‘drug abuse’ had no effect on cryptorchidism risk. While marijuana use by males has been reported to be associated with testicular cancer, 128–131 there have been no studies to date examining maternal use of marijuana and cryptorchidism.…”
Section: Drugsmentioning
confidence: 99%
“…They demonstrated that the expression of the epithelial marker EpCAM decreased in migratory cells compared to those remaining in the spheroid, indicating that cells had undergone EMT, as occurs in vivo . Similarly, the transition of breast cancer cells to an invasive phenotype was shown to lead to collagen remodeling and was promoted by human mammary fibroblasts[107, 108]. Other microfluidic studies have shown that invasion of single cancer cell lines into hydrogels increases with increasing metastatic potential[16], either under hypoxia[109] or in the presence of C-X-C motif chemokine 12 (CXCL12) or matrix metalloproteinases (MMP) inhibitors[16].…”
Section: Figmentioning
confidence: 99%